Bacteriuria in Pregnancy in a Danish Contemporary Cohort of Women - Vinnie H. Greve; Thomas Greve; Rikke B. Helmig (Hindawi Limited, 2020)
Introduction. The purpose of this study is to describe bacteriuria with regard to the uropathogens found in relation to the frequency of urine culture tests in a contemporary cohort of pregnant Danish women. Methods. A historical cohort study of 24,817 pregnant women registered in the Danish Fetal Medicine Database at Aarhus University Hospital, from 2010 to 2014. Social security numbers were linked to the microbiological database with the registration of 17,233 urine cultures in 8,807 women. Bacteriuria was defined as 1×105 CFU/ml, with a maximum of two urinary pathogens. Streptococcus agalactiae (GBS) was included with 1×104 CFU/ml. Data are presented as numbers and proportions in percent. Logistic regression on predictors are presented as crude and adjusted odds ratios (ORc/ORa) with 95% confidence intervals (CIs). Results. 42% had a urine sample culture test at the hospital-the majority only once during pregnancy. 96% of all urine culture tests were negative. The bacteriuria incidence was 5.6%. The most frequent uropathogenic bacteria isolated were Escherichia coli (49%), GBS (29%), and Enterococci (10%). We identified subgroups of women with increased likelihood of bacteriuria during pregnancy: age<25 years, ORa 1.60 (CI 1.26 to 2.02, p<0.001); age>34 years, ORa 1.28 (CI 1.01 to 1.61, p=0.040); Afro-Caribbean origin, ORa 1.872 (CI 1.13 to 3.07, p=0.014); Asian origin, ORa 2.07 (CI 1.29 to 3.32, p=0.002); and mixed ethnicity ORa 2.34 (CI 1.23 to 4.46, p=0.010). Women delivering preterm were more likely to have an episode of bacteriuria during pregnancy OR 2.05 (CI 1.36 to 3.09, p=0.001). Conclusions. 96% of urine culture tests in pregnant women are negative. Optimized urine sampling may change this. Escherichia coli and GBS are predominant uropathogens. Younger and elder women, certain ethnical groups, and women delivering preterm seem more likely to have bacteriuria during pregnancy.